Proposing a framework for prioritising topics for Personal Health Education in Schools, to improve public and community health, to teach acute medical conditions experienced in later childhood?q - Charles EMS Green; David A Winters; Ashley K Mehmi; James SA Green (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Interest in Public Health related to school children has undergone revitalisation in the UK in recent years as stronger associations have been made between behavioural patterns initiated or that develop during childhood and the resulting health outcomes in later life [1]. This together with the rising cost of healthcare [2] has led to a further concentration on preventative approaches including education in schools, promotion of a healthy lifestyle via widespread media intervention, and increased emphasis on health screening and health checks within General Practice [3].